Trade, Growth, and the Environment - Copeland, Brian R.; Taylor, M. Scott (Journal of Economic Literature, 2004)
This essay reviews what we currently know about the environmental consequences of economic growth and international trade. Using a unified framework, we critically review both theory and empirical evidence on issues such as the Environmental Kuznets Curve, the pollution haven hypothesis, and the effects of environmental policy differences on trade and investment flows. We consider how this evidence can help us evaluate ongoing policy debates, and we discuss directions for further research.